THE USE OF AIR JETS FOR INTENSIFICATION OF THE EVAPORATION PROCESS FROM AREA OF SPILL - Biliaiev, M. M.; Mashyhina, P. B. (Science and Transport Progress, 2009)
The 2D numerical model to simulate the pollutant dispersion and evaporation, when the air jet is used, was proposed. The results of numerical experiment are presented.